Optimizing animal care through compound feed management in Saudi Arabia - Alnafissa, Mohamad; Alotaibi, Bader Alhafi; Aldawdahi, Nageeb; Imran Azeem, Muhammad; Muddassir, Muhammad (Frontiers in Sustainable Food Systems, 2024)
Proper animal feeding practices play a fundamental role in enhancing livestock health and maximizing output. Given the governmental restrictions on green fodder cultivation in Saudi Arabia (SA) due to water conservation efforts, the use of compound feed could serve as a viable alternative for livestock farmers. This study aimed to investigate livestock farmers' farming objectives, their feeding management strategies, and the uptake of compound feed in the country.Data from 650 randomly selected livestock farmers were collected through an online survey with the assistance of the Ministry of Environment, Water and Agriculture. The findings showed that most farmers raised sheep and goats for trade purposes using specialized farms and desert grazing.Alfalfa hay was widely used as a fodder along with barley grain. While approximately 47% of the farmers did not utilize compound feed, 44% reported its usage. Binary logistic regression analysis indicated that formal education, farming experience, and income level significantly influenced the adoption of compound feed among livestock farmers. These results underscore the critical role of education and financial resources in promoting the use of compound feed among livestock farmers in SA. It is recommended that government institutions should develop initiatives to educate farmers on proper animal nutrition practices and provide financial support to make compound feed more affordable for low-income farmers. The widespread use of compound feed has the potential to enhance livestock health and productivity, thereby positively contributing to the food security of SA.